Evaluation of the efficiency of a septic tank combined with anaerobic filter, filled with plastic residue, including a root zone - Lira, Vivian Silva [UNESP]; Freire, Alice Gabriela; Fracácio, Renata [UNESP]; Morais, Leandro Cardoso [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2020)
Considering the damage resulting from in natura disposal of waste in soil or water bodies, we installed an alternative system of domestic effluent treatment consisting of a septic tank combined with an anaerobic filter, including a root zone. System efficiency was evaluated based on physical, chemical, and biological analyses, in addition to ecotoxicological tests (toxicity tests with Ceriodaphnia dubia). Conductivity values decreased from 3380 to 561 µS cm-1 (83.4%) after treatment. Average organic matter removal efficiency was 88.75% and there was a significant decrease in BOD. Phosphorus removal percentage was 97.68%, while nitrogen removal percentage was 94.7%. Toxicity tests determined an LC50 = 1.70% for the raw effluent and an LC50 = 16.63% for the treated effluent. The system achieved good efficiency in reducing all analyzed parameters. The use of a plastic residue as a filter element in the anaerobic filter proved to be feasible.
Keywords: Anaerobic filter; Conduits; Root zone; Septic tank